Estudo de desempenho de eficiência retrorrefletiva de películas empregadas em sinalização vertical - Vieira, Rossano Streppel (2020)
The good visibility of traffic signs is of essential importance so that drivers can perceive them and carry out the most appropriate actions for the safety of themselves and other drivers. However, it is sometimes possible to observe signs that, during the day, are visible and look good, but that, at night, their colors do not transmit the same information. One of the existing methods for estimating the ability of the retroreflective sheeting to be viewed at night is the retroreflective readings performed with portable measuring devices. This research aims to measure and analyze the results of retroreflectivity of sheetings used in traffic signs implemented in the experimental segment located in the city of Santa Maria/RS, in addition to evaluating, in the laboratory, the behavior of these retroreflective sheeting. The experimental segment has 24 signs in four different colors and three types of retroreflective sheeting, according to the NBR 14644 (2013) standard. A sign of the same color and of the same type was duplicated to observe the effect of dirt over time, since one was cleaned with water and neutral soap and the other was not. In the comparison between colors, types of sheeting and cleaning, it was found that, in relation to the loss of retroreflectance, only cleaning proved to be a statistically significant factor in the 75 months (6.27 years) of analysis. Based on the predictive models generated in this study for the sheeting exposed in the experimental segment, the set of sheetings without cleaning showed, on average, a loss of retroreflectance in relation to the initial measurement about 7 times greater than the set of sheetings that received regular cleaning . Regarding the correlation between the retroreflective performance of sheetings tested in an accelerated artificial aging equipment (Suntest XLS +) and field measurements, there was no exact correlation between the behavior of the two tests, since there was a distinct behavior between the measurements obtained field and those tested on the Suntest XLS +, for a 1.5-year boundary condition of accumulated radiation (300-800nm). However, in comparison, the correlation between the retroreflective measures and the accumulated radiation exposed sheetings in the Suntes XLS + showed a greater correlation between these two variables than in the field. It was observed that meteorological phenomena, such as rainfall, were not shown to be significant factors in the cleaning of the retroreflective sheetings and, consequently, neither in the increase of the measured values of retroreflective. The temperature of the sheeting was shown to be influential on the retroreflectivity. Evaluating the sheetings exposed in the monitored segment during a day, it was verified, for a variation of 25ºC in the temperature of the sheeting, that there was a change of 20% in the retroreflectivity of the types I and X and of 40% for the type III. Comparing the predictive models found in the literature with those generated in the experimental segment, it was not noticed a percentage of annual loss in relation to the initial retrorefletivity, however the highest percentage of the models (75%) presented an annual loss between 0% and 5% in relation to your initial measurement. In addition, the time during which the models presented retrorefletivity below the minimum Brazilian and North American parameters was analyzed. For Brazilian requirements, the highest frequency of failure was between 0 to 15 years of service; for the North American, it was 5 to 20 years of activity. Sheetings of types III and X were conditioned in a humid chamber, with the objective of evaluating their behavior in an environment with a high percentage of humidity. With that, it was found that the sheetings obtain, on average, an annual loss in terms of the initial retroreflectivity of 11% over the initial retroreflectivity.